Use of Facebook Platform in Providing Crime Information Campaign in North Fairview, Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Nowadays, criminals are getting wiser and better; in that case, we need to cope and think ofan immediate solution to help our city because now criminals innovate a new plan and newmodus operandi to execute their bad acts and successfully finish them. The primary aim of thisstudy is to provide information regarding the use of the Facebook platform in providing crimeinformation campaigns in North Fairview Quezon City.The study presents data on the demographic profile of the respondents, assessment of therespondents to Facebook as a provider of crime information campaign, problems encounteredby the Police officer in terms of legality of the post, acceptance of the end user, and availabilityof information and the statistical tool used were frequency and percentage, weighted mean,and Likert scale. Based on the data, the majority of the respondents are male and single, aged31 and above. In terms of the assessment by the end-user on Facebook, the legality of thepost is considered the most effective in providing factual information. Acceptance of the enduser is considered to create a connection to the community, and availability of information isconsidered to spread information efficiently. Overall, the respondents Strongly Agree thatFacebook is an effective way to provide crime information campaigns.Based on the findings of the study, it is recommended that law enforcement agencies andother organizations responsible for crime information campaigns on social media platformsshould take into account the perceptions of both citizens and police officers to design moreeffective campaigns. The law enforcement who are responsible for disseminating crimeinformation campaigns should innovate more ways to disseminate campaigns faster to thecommunity in order to make them more accessible.
Keywords: Criminology